Formation of Fiber Length in High-Generation Hybrids Obtained Through Ecological-Geographical Long-Term Hybrids (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
In this article, based on the study of the formation and stabilization of fiber length characteristics in the soil-climate field experiments of PSUEAITI of Andijan and Tashkent region of ecologically-geographically and genetically distant high-generation hybrids, the fiber length is high by involving ecologically-geographically distant forms in hybridization. It was determined that it is possible to isolate families and achieve positive results in high-generation hybrids, and the obtained results are reflected in the article.